The Digitalization of EU’s Diplomacy – Features of Economic Diplomacy - Cătălina Bratosin-Vasilache; Liviu-George Maha (Romanian Journal of European Affairs)
Technological advancements, alongside the constant evolution and expansion of the topics which are analysed at the global level, have contributed to the metamorphosis of public diplomacy, in an effort to address the contemporary global challenges. Nowadays, diplomatic practices are subject to a continuous process of digitalization that makes use of tools that not only enhance communication and outreach, but also strive to improve cost effectiveness and operational efficiency. Nevertheless, it cannot be overlooked that the digitalization of diplomacy also gives rise to a number of modern issues, such as cybersecurity threats or disinformation, which are shaped by each region’s particular geopolitical and economic factors. Therefore, the purpose of this paper is to explore the implications of digitalization in diplomacy, exposing both its opportunities and threats, underlying the particularities of European economic diplomacy. In order to thoroughly analyse the existing scientific research on the matter and with the intention of offering an in-depth perspective and understanding of the digitalization of European economic diplomacy, a systematic literature review has been conducted, of the refereed articles, published between 2013-2025 in high-impact journals